Tessellations on bidimensional materials based on phthalocyanine and applications: a review - del Castillo Vázquez, Roxana Mitzayé; Parga-Fuentes, Carolina; Duran-Toribio, José M.; Calles, Alipio (Mundo Nano. Revista Interdisciplinaria en Nanociencias y Nanotecnología, 2022)
In this review, we explore the bidimensional materials based on phthalocyanine molecules. The phthalocyanine molecule is used as a brick for the construction of new bidimensional materials. In particular, the phthalocyanine molecules can be placed at each vertex or sharing edges to form tessellations. The tessellations available are constrained to the four-fold type of the phthalocyanine molecules and can be a mix of several polygons to increase the number of possibilities. Computationally, the popular tessellations used are the Archimedean tiling, but many others expect to be discovered and well-studied. Different tessellations will provide new symmetric systems to explore. Each new symmetry pattern will modify the physical and chemical properties of the new bi-dimensional material. These new materials present many exciting applications as capture and storage of greenhouse gases and molecular electronic devices. In the present review, we summarized some of these tessellations and the many applications that they can have.